PERBANDINGAN SISTEM HUKUM DI INDONESIA DENGAN HUKUM ISLAM DI ARAB SAUDI TENTANG PIDANA MATI - Busri, Ihsan; Gultom, Elfrida Ratnawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Southeast Asian nation of Indonesia enacted a Civil Law legal system heavily inspired by Western law. While Saudi Arabia, which upholds Islamic law, based its rules directly on the Qur'an and Hadith, both of which support the death sentence, the Indonesian legal system bases its laws primarily on legislation. The goal of this study is to determine the parallels and differences between the death penalty's application in Saudi Arabia and Indonesia, as well as the elements that make these two countries' applications distinct from one another. Normative legal research is the kind of research employed in this investigation. The historical and comparative approaches that were employed in this study are historical and comparative approaches, respectively. The study's conclusions indicate that Saudi Arabia and Indonesia apply the death sentence in quite comparable ways. In spite of this, Indonesia and Saudi Arabia employ rather different criteria when deciding whether to execute someone. Historical elements contribute to both Saudi Arabia's and Indonesia's criminal law systems' similarities and variances. While Indonesia employs a Civil Law legal system, which makes legislation the primary source of law, Saudi Arabia implements an Islamic legal system based on the Qur'an and Hadith.Keywords: Death penalty, Qhisas and Comparison Of Legal Systems